Evaluation of health promotion actions within The Federal Public Service - de Moura, Joelma dos Reis Soares (Seven Editora, 2023)
The present work deals with actions to promote public health in the federal service, analyzing issues of administrative law and raising the hypothesis whether such actions constitute public policies in relation to this sector. For this, it uses doctrines, information from public agencies, other studies already carried out and legislation. The research is of the exploratory type with documentary and bibliographic source. This study concludes considering that these practices offered by the Federal Public Administration to the federal public servant, are not characterized as public policies, since they are presented in a timely and differentiated manner in the different federative units of the Integrated Subsystem of Attention to the Health of the Server (SIASS).it possible to transform fun into learning. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-158